PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PT. CHAROEN POKPHAND JAYA FARM 7 DESA SAMPE CITA KECAMATAN KUTALIMBARU - Barus, Winshi Agatha; Sagala, Edison (Relawan Jurnal Indonesia, 2024)
This study aims to analyze the influence of work environment and incentives on employee performance at PT Charoen Pokphand Jaya Farm 7, located in Sampe Cita Village, Kutalimbaru District. This study uses a quantitative method with a total sampling approach, where the entire population of 85 employees is used as respondents. Data analysis was carried out using multiple linear regression with the help of SPSS 25 software. The results of the study indicate that the work environment and incentives have a positive and significant influence on employee performance.